A Fuzzy Comprehensive Evaluation-Based Information Security Risk Assessment of Online Threats Among Young Individuals: A University Campus Scenario - Aliu, Folasade (Journal of Science and Technology, 2026)
This research conducts a comprehensive examination of the online threats encountered by young individuals, particularly students, at a University. Utilizing a detailed information security risk assessment approach, the study identifies and analyzes various online risks faced by students, including cyberbullying, exposure to inappropriate content, online predators, privacy breaches, and device security vulnerabilities. The research employs both quantitative and qualitative methods, such as surveys, interviews, and data analysis, to gain insights into the prevalence, nature, and impact of these online threats on the university’s student population. The level of information security risks experienced by students was evaluated using Risk Matrix, Entropy, and Fuzzy Comprehensive Evaluation (FCE) methods. The results indicate that the students’ information security risk level falls within the low category among five defined risk levels, with an FCE output of 0.403. Additionally, the study proposes recommendations for enhancing the university’s cybersecurity posture and promoting digital safety among students. This case study contributes to the broader discourse on information security risk management in educational institutions and provides practical insights for addressing online threats faced by young individuals in academic settings.